Asparaginyl Endopeptidase (Legumain) Supports Human Th1 Induction via Cathepsin L-Mediated Intracellular C3 Activation - Freeley, Simon; Cardone, John; Günther, Sira C.; West, Erin E.; Reinheckel, Thomas; Watts, Colin; Kemper, Claudia; Kolev, Martin V. (Frontiers in Immunology, 2018)
Autocrine activation of the complement receptors C3aR and CD46 by complement activation components C3a and C3b produced through C3 cleavage by the protease cathepsin L (CTSL) during T cell stimulation is a requirement for IFN- production and Th1 induction in human CD4+ T cells. Thus, lack of autocrine CD46 activation, such as in CD46- and C3-deficient patients, is associated with defective Th1 responses and recurrent infections. We have identified LGMN (the gene coding for legumain, also known as asparaginyl endopeptidase (AEP)) as one of the key genes induced by CD46 co-stimulation during human CD4+ T cell activation. AEP processes and activates a range of proteins, among those α1-thymosin and CTSL, which both drive intrinsically Th1 activity – but has so far not been described to be functionally active in human T cells. Here we found that pharmacological inhibition of AEP during activation of human CD4+ T cells reduced CTSL activation and the CTSL-mediated generation of intracellular C3a. This translated into a specific reduction of IFN-γ production without affecting cell proliferation or survival. In line with these findings, CD4+ T cells isolated from Lgmn–/– mice also displayed a specific defect in IFN-γ secretion and Th1 induction. Furthermore, we did not observe a role for AEP-driven autocrine α1-thymosin activation in T cell-derived IFN-γ production. These data suggest that AEP is an ‘upstream’ activator of the CTSL-C3-IFN-γ axis in human CD4+ T cells and hence an important supporter of human Th1 induction.